A Rare Case of Bilateral Spaghetti Injuries in Children due to Assault by Mother and Analysis of Functional Outcome at Three Years - Lad, Parag B.; Venkateshwaran, N.; Thatte, M. R.; Tanpure, Sanket (Journal of Hand and Microsurgery, 2021)
Management of child abuse with flexor tendons, neurovascular injuries, and life-threatening conditions is challenging. It needs a multisectoral coordinated and synchronized team effort for successful outcomes. We present a case series of children abused by a parent with a sharp object. The children sustained multiple flexor tendon injuries, neurovascular injuries in upper limbs, and tracheal injury compromising respiration. We performed a tracheostomy to save a child and subsequently repaired numerous flexor tendons, nerves, and arteries. During follow-up, these children required secondary reconstruction (tenolysis, tendon lengthening, nerve reconstruction) for flexor contractures, stiffness, and sensory loss in distal forearms. We measured the range of movements and assessed the children's functional outcome using the Strickland score at 3-year follow-up. The range of movement and functional outcome was excellent in both children in our series. A timely performance of surgery, aided with efficient intensive care, therapy, and consistent posttraumatic psychosocial rehabilitation, produced excellent results in our series.
Keywords: pediatric spaghetti injury; bilateral; maternal child assault